VAT and its Influence on Buying Behaviour - Vladimira Kucerova (Institute of Economic Research (IER), 2017)
Value added tax, as an instrument of fiscal policy and also a very important income for the state budget. It is one of the universal indirect taxes, which has a significant influence on the price level in the country. The European Union's system of value added tax on goods and services are primarily governed by "the 6th VAT Directive" set by the European Commission. The paper deals with the question of how changes in the rates of value added tax influence buying behaviour of customers. Buying behaviour could be expressed as decisions of customers about expending their own resources such as money, effort and time, on items related to their consumption in order to meet their needs. The area of the research is a Czech retail market with food. Due to the nature of VAT, the influence of this tax on buying behaviour was quantified by price elasticity of demand respectively indirect tax elasticity of demand. The article is conceived as a case study, according to the principles R.K. Yin. The evaluation of buying behaviour is based on real data, which deals with volumes of sales and sales prices realized in a specific Czech retail chain, which associate more than 200 shops. The goal of the study is not only to propose the way how to identify buyers' response to the changes in the VAT rate, but also to bring the knowledge about customers' response to the realized changes, and finally to propose how to use this knowledge in a development of pricing strategy in case of further changes in the VAT rate.
Keywords: D12; H31; E62; 330; Value Added Tax; price elasticity of demand; buying behavior; food retail; case study